The Transformation of Islamic Democracy in the Digital Era: A Critical Study on the Role of Ulama in the Virtual Public Sphere - Situmorang, Jubair (Side: Scientific Development Journal, 2025)
The advent of the digital era has brought transformative changes across various sectors of society, including politics, religion, and culture. One of the most significant developments in this context is the transformation of Islamic democracy, particularly the evolving role of ulama (Islamic scholars) in shaping political discourse in the virtual public sphere. This study critically examines how Islamic democracy is being redefined in the digital age, with a specific focus on the participation of ulama in online platforms and their influence on public opinion and political engagement among Muslim communities. The research delves into the ways in which social media, digital forums, and online discourse provide a space for ulama to engage with a broader audience, facilitating the dissemination of Islamic political thought and contributing to democratic practices within Muslim societies. The study employs a qualitative approach, analyzing both primary data, such as interviews with ulama and key stakeholders, and secondary sources, including digital content, scholarly articles, and political discourse. It explores how the ulama have adapted to the digital landscape, balancing traditional interpretations of Islam with the dynamic and interactive nature of online communication. By doing so, the paper addresses critical questions about the potential of the virtual public sphere in promoting or hindering democratic values within Islamic societies, examining the balance between religious authority and democratic participation. The findings highlight the significant role of ulama in shaping public opinion, guiding political discourse, and fostering civic engagement in the digital realm. It also reveals the challenges and opportunities faced by Islamic scholars in navigating the complexities of digital communication while maintaining their religious legitimacy. Furthermore, the study discusses the implications of these transformations for the future of Islamic democracy and the role of ulama in influencing political decision-making in the digital age. This research contributes to the broader understanding of the intersection between religion, politics, and digital media, offering insights into the evolving nature of Islamic democracy in the 21st century.